2020
DOI: 10.1021/acsami.0c10968
|View full text |Cite
|
Sign up to set email alerts
|

Dewetting of PtCu Nanoalloys on TiO2 Nanocavities Provides a Synergistic Photocatalytic Enhancement for Efficient H2 Evolution

Abstract: We investigate the co-catalytic activity of PtCu alloy nanoparticles for photocatalytic H2 evolution from methanol-water solutions. To produce the photocatalysts, a few nm-thick Pt-Cu bilayers are deposited on anodic TiO2 nanocavity arrays and converted by solid state dewetting, i.e. a suitable thermal treatment, into bimetallic PtCu nanoparticles. XRD and XPS results prove the formation of PtCu nanoalloys that carry a shell of surface oxides. XANES data support Pt and Cu alloying and indicate the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 74 publications
1
23
0
Order By: Relevance
“…1c), which is 0.3 eV lower than that for TiO 2 -Pt0Cu1, and the other samples showed the same trend, implying a strong interaction between Pt and Cu and the formation of the PtCu alloy. 43,44 Fig. 1d shows the TEM images of the TiO 2 -Pt0.4Cu0.6 samples.…”
Section: Resultsmentioning
confidence: 99%
“…1c), which is 0.3 eV lower than that for TiO 2 -Pt0Cu1, and the other samples showed the same trend, implying a strong interaction between Pt and Cu and the formation of the PtCu alloy. 43,44 Fig. 1d shows the TEM images of the TiO 2 -Pt0.4Cu0.6 samples.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been found that for the Pt–Cu co-catalyst on TiO 2 , it has been observed there is a synergistic activity enhancement and a significantly higher activity toward photocatalytic H 2 evolution with respect to the monometallic Pt– or Cu–TiO 2 catalysts . These authors proposed that the enhanced activity could be due to Pt–Cu electronic interactions, where Cu increases the electron density on Pt, favoring a more efficient electron transfer for H 2 evolution.…”
Section: Results and Discussionmentioning
confidence: 99%
“…71,72 Indeed, it has been found that for the Pt−Cu co-catalyst on TiO 2 , it has been observed there is a synergistic activity enhancement and a significantly higher activity toward photocatalytic H 2 evolution with respect to the monometallic Pt− or Cu−TiO 2 catalysts. 73 These authors proposed that the enhanced activity could be due to Pt−Cu electronic interactions, where Cu increases the electron density on Pt, favoring a more efficient electron transfer for H 2 evolution. We note that a small amount of Pd incorporated into Cu promotes H adsorption at all coverages examined, while the Cu-core− Pd-shell structure with a significantly higher Pd content promotes HER at moderate hydrogen coverages and is less favorable at the lowest and highest H coverages.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Nanoporous TiO 2 arrays were prepared by anodizing a Ti substrate. , Prior to anodization, the titanium samples were degreased by sonication in acetone, ethanol, and deionized water for 15 min in each solvent. The Ti substrates were dried in a nitrogen stream.…”
Section: Methodsmentioning
confidence: 99%